Verbal task demands are key in explaining the relationship between paired-associate learning and reading ability - Clayton, F; Sears, C; Davis, A; Hulme, C (Elsevier, 2018)
Paired-associate learning (PAL) tasks measure the ability to form a novel association between a stimulus and a response. Performance on such tasks is strongly associated with reading ability, and there is increasing evidence that verbal task demands may be critical in explaining this relationship. The current study investigated the relationships between different forms of PAL and reading ability. A total of 97 children aged 8–10 years completed a battery of reading assessments and six different PAL tasks (phoneme–phoneme, visual–phoneme, nonverbal–nonverbal, visual–nonverbal, nonword–nonword, and visual–nonword) involving both familiar phonemes and unfamiliar nonwords. A latent variable path model showed that PAL ability is captured by two correlated latent variables: auditory–articulatory and visual–articulatory. The auditory–articulatory latent variable was the stronger predictor of reading ability, providing support for a verbal account of the PAL–reading relationship.